Zeglamia: a Code among the People of Constantine - Benlaksira , Faiza (Journal of Human Sciences, 2023)
Ludlings, or language games, have been observed all over the world to conceal speech or for entertainment purposes. In Algeria, in the city of Constantine speakers use a language variety known as Constantine dialect. A communication code called Zeglamia is used among a minority within the speech community. Lack of interest in Algerian dialectological studies dealing with ludlings is the principle reason for these varieties being stigmatized and under-resourced. The primary goal of this study is to allow the validation of this code’s existence and help preserving it as common heritage. This paper aims to understand this linguistic phenomenon and discern the reasons for which the interlocutors adopt it by means of examination and the observation of the rules involved in its creation and formation process. Zeglamia speakers are interviewed to discover the source of the code acquisition and the settings and objectives of use. Their speech is also analyzed to determine the different mechanisms. The findings can be summed up in the generation of Zeglamia’s definition and the identification of the mechanisms which are involved in the creation of its varieties.